The Contribution of Leadership Vigilance to the Implementation of Functional Tasks by Administrators of Local Volleyball Championships - Sehen , Khairiyah (Journal of Physical Education, 2025)
The present study aimed to develop two measurement scales—one for leadership vigilance and another for the implementation of functional tasks—in the context of managing local volleyball championships. It further sought to assess the levels of these two variables from the perspective of administrators, and to examine the contribution and effect of leadership vigilance on task execution. The descriptive correlational method was employed in line with the nature of the research problem. The study population comprised 141 administrators of local volleyball championships during the 2024/2025 sports season, all of whom were deliberately included (100%) through comprehensive enumeration and divided into three subsamples according to the study requirements. After constructing the two scales, they were applied to the participants, and the results were analyzed using SPSS. The findings confirmed the validity of the scales for measuring leadership vigilance and functional task implementation. Results revealed that administrators demonstrated acceptable levels in both domains, and that higher leadership vigilance was significantly and positively correlated with improved task implementation. The study concluded that leadership vigilance plays an essential role in enhancing administrators’ effectiveness in managing volleyball championships. Accordingly, the researcher recommended focusing on specialized measurement and professional development programs to strengthen leadership vigilance, thereby improving task performance and contributing to the overall advancement of federation management.